Triggers of consumer purchasing decisions by the brand image with product quality moderating empirical studies on fastron ecogreen products - Udin Bahrudin; Nurparija Nurparija; Didit Haryadi (Jurnal Mantik, 2023)
The tight business competition in the product and service industry requires companies to be able to create something different. This study aims to test and analyze improving purchasing decisions on Fastron Ecogreen brand oil products which are influenced by brand image and moderated by product quality. The method used in this research is the descriptive quantitative method with a survey approach. 150 research sample respondents. Survey of research objects in three attack workshops that use Fastron Ecogreen lubricants. The results of this study indicate that brand image has a significant effect on purchasing decisions, product quality has a significant effect on buying decisions, and product quality can moderate significantly strengthen the influence of brand image on purchasing decisions. In this context, this research is expected to make a theoretical contribution to the literature